Integrasi Kewirausahaan dalam Manajemen Pendidikan Islam: Tinjauan Literatur - Yuli Supriani; Rachmat Panca Putera; Ali Mustofa; Reni Adha Ningrum; Linda Desi Yana; Fajar Nuriman (Pusat Riset dan Inovasi Nasional, 2025)
This article discusses the integration of entrepreneurship in Islamic education management through a literature review approach. The purpose of this study is to identify the concepts, challenges, and implementation strategies of entrepreneurship grounded in Islamic values within the management of Islamic educational institutions. The review reveals that entrepreneurship in Islamic education is not solely oriented towards economic aspects but also emphasizes ethical values such as honesty, trustworthiness, and social responsibility. Such integration has the potential to enhance the independence, innovation, and sustainability of Islamic educational institutions. However, structural and cultural barriers remain significant challenges that must be addressed through strengthening entrepreneurship curricula based on Islamic principles, capacity building of human resources, and supportive institutional policies. This study concludes that the integration of entrepreneurship in Islamic education management is a strategic necessity to respond to the dynamics of modern education and to develop adaptive and visionary institutions.